A comparative analysis of the DNA recombination repair pathway in mycobacterial genomes. (July 2016) - Singh, Amandeep; Bhagavat, Raghu; Vijayan, M.; Chandra, Nagasuma
Summary: In prokaryotes, repair by homologous recombination provides a major means to reinstate the genetic information lost in DNA damage. Recombination repair pathway in mycobacteria has multiple differences as compared to that in E scherichia coli . Of about 20 proteins known to be involved in the pathway, a set of 9 proteins, namely, RecF, RecO, RecR, RecA, SSBa, RuvA, RuvB and RuvC was found to be indispensable among the 43 mycobacterial strains. A domain level analysis indicated that most domains involved in recombination repair are unique to these proteins and are present as single copies in the genomes. Synteny analysis reveals that the gene order of proteins involved in the pathway is not conserved, suggesting that they may be regulated differently in different species. Sequence conservation among the same protein from different strains suggests the importance of RecO-RecA and RecFOR-RecA presynaptic pathways in the repair of double strand-breaks and single strand-breaks respectively. New annotations obtained from the analysis, include identification of a protein with a probable Holliday junction binding role present in 41 mycobacterial genomes and that of a RecB-like nuclease, containing a cas4 domain, present in 42 genomes. New insights into the binding of small molecules to the relevant proteins are provided by binding pocket analysis using three dimensional structural models. Analysis of the various features of the recombination repair pathway, presented here, is likely to provide a framework for further exploring stress response and emergence of drug resistance in mycobacteria.